2017
DOI: 10.1371/journal.pone.0170809
|View full text |Cite
|
Sign up to set email alerts
|

Tuna Species Substitution in the Spanish Commercial Chain: A Knock-On Effect

Abstract: Intentional mislabelling of seafood is a widespread problem, particularly with high-value species like tuna. In this study we examine tuna mislabelling, deliberate species substitution, types of substitution and its impact on prices. The survey covered the commercial chain, from Merca-Barna to fishmongers and restaurants in the Spanish Autonomous Community of Catalonia. To understand the geographic extent of the problem we also sampled Merca-Madrid, Europe’s biggest fish market, and Merca-Málaga for its proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Sampling at each collection site/ area so far has remained small scale (n ≤ 11, Barth et al, 2017;n ≤ 24, Grewe et al, 2015;n ≤ 45, Pecoraro et al, 2018;n ≤ 80, Anderson et al, 2019), and the number of sites in the Pacific are limited (n = 2, Barth et al, 2017;n = 3, Grewe et al, 2015;n = 4, Pecoraro et al, 2018;n = 7, Anderson et al, 2019). Nonetheless, DNA profiling is expected to gain widespread use for its utility in addressing illegal fishing and seafood mislabeling (Gordoa et al, 2017). Given our results that yellowfin are highly mobile over a short period of time, particular attention should be given to DNA sampling design to account for spatiotemporal factors from seasonal movements of multiple size classes, to changing oceanographic conditions (e.g., currents, temperature, monsoon) and coupled systems (e.g., ENSO).…”
Section: Horizontal Movement and Stock Structurementioning
confidence: 99%
“…Sampling at each collection site/ area so far has remained small scale (n ≤ 11, Barth et al, 2017;n ≤ 24, Grewe et al, 2015;n ≤ 45, Pecoraro et al, 2018;n ≤ 80, Anderson et al, 2019), and the number of sites in the Pacific are limited (n = 2, Barth et al, 2017;n = 3, Grewe et al, 2015;n = 4, Pecoraro et al, 2018;n = 7, Anderson et al, 2019). Nonetheless, DNA profiling is expected to gain widespread use for its utility in addressing illegal fishing and seafood mislabeling (Gordoa et al, 2017). Given our results that yellowfin are highly mobile over a short period of time, particular attention should be given to DNA sampling design to account for spatiotemporal factors from seasonal movements of multiple size classes, to changing oceanographic conditions (e.g., currents, temperature, monsoon) and coupled systems (e.g., ENSO).…”
Section: Horizontal Movement and Stock Structurementioning
confidence: 99%
“…The mislabelling rate was not significantly different (Chi-square = 0.1045; df = 1; P = 0.3733) between fresh & frozen and canned tuna, 6.70% and 7.84%, respectively, while the miscellaneous products showed 1.92% mislabelling (not significative differences among them). Previous works have reported higher mislabelling rates, recently Gordoa et al [ 16 ] have shown that fresh and frozen tuna in Spain was mislabelled up to 37% at points of sale, while in restaurants the mislabelling rate was even higher, 48%. In a previous report from Oceana [ 28 ], tuna samples obtained at different points of the value chain in different states of the USA showed that 58% of tuna products were mislabelled.…”
Section: Methodsmentioning
confidence: 98%
“…These results agree with the results found by Vandamme et al [ 29 ] that reported a low mislabelling rate for tuna in sushi of about 10%, but which rises up to 18% when tuna species is considered in the labelling. Likewise, Gordoa et al [ 16 ] reported a 73% of mislabelling for Atlantic Bluefin tuna and points towards economic gain as the main reason for mislabelling tuna. Atlantic Bluefin mislabelling has been highlighted as an example of inverse relationship between low volume catches and high proportion of substitution; offer and demand do not match and the result is a very high mislabelling rate [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations